Distant metastatic lesions in patients with differentiated thyroid carcinoma - Hong, C. M.; Ahn, B.-C.; Jeong, S. Y.; Lee, S.-W.; Lee, J. (Nuklearmedizin - NuclearMedicine, 2013)
Aim: Many investigators have reported an inverse relationship between iodine and glucose utilization of differentiated thyroid carcinoma (DTC) according to its degree of differentiation; however, not every DTC is compatible with this phenomenon. This study was conducted to evaluate the clinical implication of iodine and glucose uptake at distant metastatic lesions in DTC patients. Patients, methods: 64 DTC patients (women 47; mean age 49.9 ± 16.4 years) with distant metastasis who underwent post 131I treatment whole-body scan (RxWBS) and FDG PET/CT were included in the study. Radioiodine (RAI) and FDG uptake of metastatic lesions were evaluated. TSH stimulated serum thyroglobulin (s-Tg) were obtained. Results: 53 of 64 patients (82.8%) were RAI(+) group, and 37 patients (57.8%) were FDG(+) group. Patients in the RAI(–) group showed a higher rate of FDG uptake than RAI(+) group (100.0% vs. 49.1%, p = 0.002). Patients in the FDG(–) group showed a higher rate of RAI uptake than FDG(+) group (100.0% vs. 70.3%, p = 0.002). Patients with s-Tg < 100 ng/ml were frequently observed in the FDG(–)/RAI(+) group and the FDG(+)/ RAI(–) group (p = 0.023). And patients with s-Tg ≥ 500 ng/ml were more frequently observed in the FDG(+)/RAI(+) group, compared with the FDG(+)/RAI(–) group (p = 0.036). Reduced disease-specific survival (DSS) was observed in patients with RAI(–) (p = 0.003), FDG(+) (p = 0.006), SUVmax > 3.6 (p<0.001), and s-Tg > 75.8 ng/ml (p = 0.009). In multivariate analysis, only a SUVmax > 3.6 was significantly predictive of DSS (p = 0.006). Conclusion: An inverse relationship between RAI and FDG uptake, flip-flop phenomenon, was observed in patients with metastatic lesions of DTC. Reduced disease-specific survival was observed in patients with FDG(+), RAI(–) in metastatic lesions, or high s-Tg value.
Keywords: Flip-flop phenomenon; FDG; iodine; differentiated thyroid cancer; survival